EFFECT OF RIVETING ON THE JOINT STRENGTH OF ADHESIVELY BONDED DOUBLE LAP JOINTS - Solmaz, M. Yavuz; Kocabaş, İbrahim; Gür, Mustafa (My University, 2018)
The scope of this study is to determine the effectiveness of using rivets in the adhesive joints in order to combine plastic-basedcomposite materials which are often used in today's engineering structures, to the joint strength. For this purpose, double lapjoints are prepared in 3 different types of configuration included adhesive, pinned and both adhesive and pinned and alsoprepared in 3 different overlap lengths as 30, 45 and 60 mm. Stress-strain diagrams were derived by exposing the jointsobtained, to the axial tensile test and then the most appropriate joint type was determined by comparing each of the resultsobtained. The evaluation of the results pointed out that the hybrid joints where adhesive and rivet are used together can carrymuch more load than the joints where the only adhesive was used or the joints which are combined with a rivet in terms of jointstrength.
Keywords: Mühendislik; Makine